2007
DOI: 10.1016/j.virol.2007.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Variola virus topoisomerase: DNA cleavage specificity and distribution of sites in Poxvirus genomes

Abstract: Topoisomerase enzymes regulate superhelical tension in DNA resulting from transcription, replication, repair, and other molecular transactions. Poxviruses encode an unusual type IB topoisomerase that acts only at conserved DNA sequences containing the core pentanucleotide 5'-(T/C)CCTT-3'. In X-ray structures of the variola virus topoisomerase bound to DNA, protein-DNA contacts were found to extend beyond the core pentanucleotide, indicating that the full recognition site has not yet been fully defined in funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…The sequence of the -3 to -1 region of the vTopIB target site has been shown to have minimal effects on non-covalent binding of the enzyme, but strongly influences the rate of DNA cleavage (Hwang et al, 1999; Hwang et al, 1998; Minkah et al, 2007; Shuman and Prescott, 1990). These sequence preferences can be readily explained by the observed α10a contacts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence of the -3 to -1 region of the vTopIB target site has been shown to have minimal effects on non-covalent binding of the enzyme, but strongly influences the rate of DNA cleavage (Hwang et al, 1999; Hwang et al, 1998; Minkah et al, 2007; Shuman and Prescott, 1990). These sequence preferences can be readily explained by the observed α10a contacts.…”
Section: Resultsmentioning
confidence: 99%
“…The variola virus topoisomerase (which differs by only three amino acids from the vaccinia virus protein) has also been well-studied, including a detailed analysis of sequence preferences in the regions flanking the core pentanucleotide motif (Minkah et al, 2007). An analysis of TopIB cleavage sites has revealed a distribution throughout the poxvirus genomes, with a central clustering of sites observed only for the orthopox viruses (Minkah et al, 2007). The poxvirus topoisomerases are part a broader family of small type IB enzymes which includes the topoisomerases from mimi virus and a number of eubacteria (Benarroch et al, 2006; Krogh and Shuman, 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…3a-b) opposite the catalytic domain. Interestingly, even with homologous DNA-binding domains, TopIB enzymes of some viral origins have DNA sequence preferences (Shuman and Prescott, 1990; Perry et al, 2006; Minkah et al, 2007), while others, e.g. human topoisomerase I, are non-sequence specific (Redinbo et al, 1998; Champoux, 2001).…”
Section: Similarity Between Topib and Yrsmentioning
confidence: 99%
“…The DNA sequences used in the current study contain a T at the −1 position relative to the cleavage site. Although previous work has shown that an A at this position accelerates cleavage by about 10-fold relative to T, this substitution does not change the cleavage equilibrium and it facilitates singleturnover kinetic measurements by hand mixing (9, 13). The nature of the base at the -1 position has no bearing on the interpretations of this study.…”
Section: Materials and Methods1mentioning
confidence: 89%